MICROBIAL NUCLEATION OF CALCIUM CARBONATE IN THE PRECAMBRIAN - Bosak T.; Newman D.K. (My University, 2003)
Microbial sulfate reduction is thought to stimulate carbonate precipitation in modern stromatolites, yet whether this metabolism was important in shaping Precambrian stromatolites is unknown. Here we use geochemical modeling to suggest that the influence of sulfate reduction on the saturation index of calcite (SI) is negligible when seawater is in equilibrium with high pCO2, as is thought for the Precambrian. Our laboratory experiments with heterotrophic bacteria in a medium mimicking Precambrian seawater chemistry show that even if sulfate reduction does not significantly change the SI, the presence of bacteria stimulates calcite precipitation over sterile controls by effectively increasing the SI over a pH range from 7.3 to 7.8. Under our experimental conditions, dead cells stimulate in situ carbonate precipitation equally, if not more, than active sulfate-reducing bacteria. Heterogeneous nucleation of calcite by microbial cell material appears to be the driving mechanism that explains this phenomenon. [PUBLICATION ABSTRACT]
Keywords: stromatolites; bacteria; nucleation; biogenic effects; Precambrian; Precambrian; Докембрий